Randai Ilau Nagari Saniang Baka: Dinamika, Makna, dan Upaya Revitalisasi Kesenian Tradisional Minangkabau - Agung Setiawan; Yunaidi Yunaidi; Muhammad Rafif (INDO PUBLISHING, 2026)
Randai Ilau is one of the traditional Minangkabau arts originating from Nagari Saniang Baka, X Koto Singkarak District, Solok Regency, West Sumatra. This art is included in the form of old randai which still maintains its traditional characteristics to this day. Unlike randai in general which developed as a folk performing art with elements of drama and dialogue, Randai Ilau has unique characteristics in the form of the use of vocal singing as the only musical element, movements derived from Minangkabau silek, and a strong connection with the community's traditional rituals. This study aims to describe the dynamics of the development of Randai Ilau, analyze the cultural meaning contained in it, and examine the revitalization efforts made to maintain its existence. The research method used is descriptive qualitative with a literature study approach. The results of the study show that Randai Ilau has experienced a development in function from ritual art to cultural performing arts that can be displayed in various social activities. In addition to having artistic value, Randai Ilau also contains social, leadership, religious, and cultural education values that are an important part of the life of the Nagari Saniang Baka community. Various revitalization programs undertaken by the government, academics, and local communities demonstrate a collective awareness of preserving this cultural heritage.